Handbook on International Alliance and Network Research 2015
DOI: 10.4337/9781783475483.00010
|View full text |Cite
|
Sign up to set email alerts
|

Transaction cost perspectives on alliances and joint ventures: explanatory power and empirical limitations

Abstract: Transaction cost economics (TCE) has been extensively applied by international business scholars to analyze joint ventures and strategic alliances. It provides a theoretical basis to analyze how firms organize their transactions with other firms, and hence their choices of governance structures, for example between JVs and other organizational forms. However, TCE has also been frequently critiqued and empirical findings on some of the constructs derived from TCE find inconsistent results. This chapter critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 101 publications
(159 reference statements)
0
9
0
Order By: Relevance
“…A fast review is a methodology accustomed describe the implications of the synthesis from numerous sorts of literature, anywhere the implications of the synthesis rectangular degree anticipated to help positive events in growing decisions [12]. This methodology square measure frequently aforesaid to be a changed form of systematic assessment that creates it ability to place operative it in abundant less time and use abundant less literature [13], than scientific assessment. moreover [14], named that changes rectangular degree generally created to gift approaches of the systematic assessment methodology in accomplishing fast reviews, a number of that rectangular degree English-most effective literature, ignoring grey literature, limiting literature get reassets, and utterly relating to one individual to settle on out literature or extract experience.…”
Section: Methodsmentioning
confidence: 99%
“…A fast review is a methodology accustomed describe the implications of the synthesis from numerous sorts of literature, anywhere the implications of the synthesis rectangular degree anticipated to help positive events in growing decisions [12]. This methodology square measure frequently aforesaid to be a changed form of systematic assessment that creates it ability to place operative it in abundant less time and use abundant less literature [13], than scientific assessment. moreover [14], named that changes rectangular degree generally created to gift approaches of the systematic assessment methodology in accomplishing fast reviews, a number of that rectangular degree English-most effective literature, ignoring grey literature, limiting literature get reassets, and utterly relating to one individual to settle on out literature or extract experience.…”
Section: Methodsmentioning
confidence: 99%
“…Strategic interfirm alliance has also been attributed to competitive advantage (Hung et al, 2015; Talebi et al, 2017; Zhao, 2014), transaction cost reduction (Brouthers, 2013; Geyskens et al, 2006; Meyer & Wang, 2004; Tihanyi et al, 2005), social capital (Ireland et al, 2002, as cited in Talebi et al, 2017), new opportunities (Joshi & Dixit, 2014 as cited in Talebi et al, 2017; Yang et al, 2014), and firm performance (Junaidu et al, 2019; Kim, 2015; Nwokocha & Madu, 2020; Talebi et al, 2017). Consequently, the background thus far has shown that strategic interfirm alliance enables firms and industries including SSIs to adapt and withstand economic challenges.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…We know that alliance governance is affected by opportunism hazards (e.g. Poppo and Zenger, 2002;Meyer and Wang, 2015). Misaligned governance in alliances could be a source of problems that negatively impact alliance performance (Sampson, 2004).…”
Section: Limitations and Possible Future Research Directionsmentioning
confidence: 99%